Positive- vs. negative-pressure extubation technique: a scoping review - Liu, Jing; Li, Fang; Qi, Xiangyang; Zhuang, Xin; Cui, Zhaomei (Frontiers in Medicine, 2023)
Objectives: This review aimed to summarize the recent literature on positive-pressure extubation. Design: A scoping review was conducted under the framework of the Joanna Briggs Institute. Data sources: Web of Science, PubMed, Ovid, Cumulative Index to Nursing & Allied Health, EBSCO, Cochrane Library, Wan Fang Data, China National Knowledge Infrastructure, and China Biology Medicine databases were searched for studies on adults and children. Study selection: All articles describing the use of positive-pressure extubation were considered eligible for inclusion. The exclusion criteria were articles not available in English or Chinese, and those without full text available. Data extraction and synthesis: The database searches identified 8,381 articles, 15 of which could be included in this review, with an aggregated patient number of 1,544. Vital signs, including mean arterial pressure, heart rate, R-R interval, and SpO2 before and after extubation; blood gas analysis indexes, including pH, oxygen saturation, PaO2, and PaCO2 before and after extubation; and incidence of respiratory complications, including bronchospasm, laryngeal edema, aspiration atelectasis, hypoxemia, and hypercapnia, were reported in the included studies. Results: The majority of these studies reported that the positive-pressure extubation technique can maintain stable vital signs and blood gas analysis indices as well as prevent complications during the peri-extubation period. Conclusions: The positive-pressure extubation technique has a safety performance similar to that of the traditional negative-pressure extubation technique and may lead to better clinical outcomes, including stable vital signs, arterial blood gas analysis, and a lower incidence of respiratory complications.